Decomposition of Carbon14 labelled ryegrass and maize under tropical conditions - Ayanaba, A.; Jenkinson, D.S. (Wiley, 1990)
This work is an extension of earlier studies on the rate of decay of plant material in the forest zone of Nigeria. Maize (Zea mays L.) leaves, uniformly labeled with 14C, were allowed to decompose for 2 yr under field conditions in an Alfisol (pH 7.0) or an Ultisol (pH 4.7). After two years, 15% of the original plant C still remained in the Alfisol. Decomposition was slower in the Ultisol, particularly during the first 26 wk. Maize leaves incorporated in soil at the beginning of the dry season initially decomposed more slowly than leaves incorporated during the wet season, but by the end of 2 yr the difference was small. Earlier experiments in Nigeria with labeled ryegrass (Lolium multiflorum Lam.) tops were continued: after 5 yr, 8% of the original ryegrass C remained in an Alfisol. After adjustment for differences in climate and soil texture, the current Rothamsted model for turnover of organic C in soil gave a close fit to the Nigerian data.